Model Tata Kelola Pendidikan Berbasis Good Governance untuk Meningkatkan Mutu Lembaga Pendidikan - Septi Susanti; Aleks Effendi; Anjun Nur Fauzan; Partono Partono (Educational Journal, 2026)
This study aims to develop an educational governance model based on "good governance" principles capable of enhancing the quality of educational institutions through an in-depth understanding of governance practices implemented within the school environment. The study is motivated by the varying quality of the implementation of good governance principles such as transparency, accountability, participation, and effectiveness in the management of educational institutions, which impacts the achievement of educational quality. A qualitative approach with a case study design was employed. Data were collected through semi-structured interviews, participant observation, and document analysis involving principals, vice-principals, teachers, educational staff, foundation administrators, school committees, and parent representatives selected via purposive and snowball sampling techniques. Data validity was ensured through source triangulation, method triangulation, member checking, and an audit trail, while data analysis utilized the interactive model developed by Miles, Huberman, and Saldaña. The findings identify four key themes: participatory leadership, transparency and accountability, stakeholder participation, and a culture of quality and continuous improvement. These four themes interact to form a good governance-based educational governance model that fosters organizational trust, collaboration, organizational learning, and the continuous improvement of educational institutions. This study contributes to enriching the field of educational governance by integrating Governance Theory and Total Quality Management (TQM), and offers practical recommendations for principals, foundations, and policymakers on developing educational governance that is transparent, accountable, participatory, and quality-oriented.